Unique 1D Cd1−xZnxS@O‐MoS2/NiOx Nanohybrids: Highly Efficient Visible‐Light‐Driven Photocatalytic Hydrogen Evolution via Integrated Structural Regulation. Issue 29 (15th January 2019) - Lin, Haifeng; Sun, Bowen; Wang, Hui; Ruan, Qinqin; Geng, Yanling; Li, Yanyan; Wu, Jiakun; Wang, Wenjing; Liu, Jie; Wang, Xun
Abstract: Development of noble‐metal‐free photocatalysts for highly efficient sunlight‐driven water splitting is of great interest. Nevertheless, for the photocatalytic H2 evolution reaction (HER), the integrated regulation study on morphology, electronic band structures, and surface active sites of catalyst is still minimal up to now. Herein, well‐defined 1D Cd1− x Zn x S@O‐MoS2 /NiO x hybrid nanostructures with enhanced activity and stability for photocatalytic HER are prepared. Interestingly, the band alignments, exposure of active sites, and interfacial charge separation of Cd1− x Zn x S@O‐MoS2 /NiO x are optimized by tuning the Zn‐doping content as well as the growth of defect‐rich O‐MoS2 layer and NiO x nanoparticles, which endow the hybrids with excellent HER performances. Specifically, the visible‐light‐driven (>420 nm) HER activity of Cd1− x Zn x S@O‐MoS2 /NiO x with 15% Zn‐doping and 0.2 wt% O‐MoS2 (CZ0.15 S‐0.2M‐NiO x ) in lactic acid solution (66.08 mmol h −1 g −1 ) is about 25 times that of Pt loaded CZ0.15 S, which is further increased to 223.17 mmol h −1 g −1 when using Na2 S/Na2 SO3 as the sacrificial agent. Meanwhile, in Na2 S/Na2 SO3 solution, the CZ0.15 S‐0.2M‐NiO x sample demonstrates an apparent quantum yield of 64.1% at 420 nm and a good stability for HER under long‐time illumination. The results presented in this work can be valuable inspirations for the exploitation of advanced materials for energy‐related applications. Abstract : Unique 1D Cd1 − x Zn x S@O‐MoS2 /NiO x nanohybrids are prepared which demonstrate a superior visible‐light‐driven photocatalytic H2 evolution activity of 223.17 mmol h −1 g −1, a high apparent quantum yield of 64.1% at 420 nm, and a good stability under long‐time illumination, owing to the optimized band alignments, increased exposure of active sites, and facilitated interfacial charge separation.